Learn the industrious and industrious working style of Ho Chi Minh - Lê Đức Thọ (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
The article researches the content of Ho Chi Minh’s diligent and industrious working style. Ho Chi Minh has set a shining example of hard work, industriousness and determination to achieve the highest efficiency. Ho Chi Minh’s working style in general and his industrious and diligent working style have become a model for the entire Vietnamese people in general and the contingent of cadres and party members in our country to follow and study.